Patient-Controlled Analgesia (PCA) with Remifentanil Versus Intermittent Epidural Boluses for Labor Analgesia - Karadjova, Dafina; Shosholcheva, Mirjana; Sivevski, Atanas; Ivanov, Emilija; Kjaev, Ivo; Dimitrov, Goran (Македонско лекарско друштво / Walter de Gruyter GmbH, 2017)
Introduction.Remifentanil is becoming more and more popular for labor analgesia as an alternative for neuro-axial anesthesia. In this study we compared the severity of pain, patient satisfaction and side effects between two different types of labor analgesia. Methods. Eightyprimiparous patients ASA I or II, atterm pregnancy, were included in the study and divided in two groups. The first group (35 patients) received intravenous remifentanil on patient control pump in bolus doses. The second group (45 patients) received intermittent epidural boluses with highly diluted local anesthetic and opioid (Bupivacain and Fentanil). We analyzed oxygen saturation (SpO2), respiration rate, heart rate, blood pressure, sedation, nausea and vomiting as well as patient pain scores and satisfaction scores through 2 different VAS. Results. Mean SpO2 was significantly lower in the PCA remifentanil group 96.2%±1.6 versus 98.2±1.2 in the epidural group. Respiratory depression (RR<9 or SpO2 <90%) was not found in both groups. Sedation scores were significantly higher in the PCA remifentanil group, P<0.05. Incidence of nausea and vomiting was similar between the two groups, without significant difference. PCA remifentanil was inferior to epidural analgesia with respect to pain scores at all time points, but without significant difference in patient satisfaction between the two groups. Conclusion. Intravenous patient-controlled analgesia with remifentanil provides satisfactory level of labor analgesia, with lower SpO2 and more sedation. It could be an excellent alternative to epidural analgesia but continuous monitoring and oxygen supply is mandatory.
Пациент-контролирана аналгезија со ремифентанил наспороти интермитентни епидурални болуси за безболно породување